(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article is dedicated to the development of optimal concrete composition for road pavements and the study of European experience. The article analyzes various types of concrete and their characteristics used in European countries. It also discusses the process of developing optimal composition and the possibilities for adapting European standards and technologies to local conditions. The consideration of ecological aspects and the use of innovative materials are of significant importance. The research findings provide recommendations aimed at improving the quality of road pavements and enhancing economic factors.